Effect of soccer specific high and low intensity aerobic training on cardiorespiratory endurance - Akeepan, S.; Sabaananth, S. (Tamilnadu Physical Education and Sports University, 2017)
Intensity and demand during soccer match increasing due to the advancement of the prodigious sports training inventions. Acclimatise to the demand of the competitions needs training modifications to tolerate extreme pressure during the competition. The objective of this study was to find out the effect of High and Low intensity aerobic training on Cardiorespiratory Endurance. To achieve the purpose forty five (N=45) soccer players were selected from Jaffna, Sri Lanka, and their age were ranged between 18 to 24 years. The subjects were divided at random in to three groups of fifteen each, group I underwent High Intensity Training [(HIT) (n=15, 50-60 min / day / three days / week over the period of twelve weeks)], group II underwent Low Intensity Training [(LIT) (n=15, 50-60 / day / three days / week over the period of twelve weeks)], and group III acted as control. Exercise intensity starts from 60 % and 80% of the maximum heart rate of the LIT and HIT respectively. 2% rule was implemented in every two weeks. Cardiorespiratory endurance was assessed by using Cooper’s 12 min run or walk test. Data were collected on cardiorespiratory endurance before and after the training period, and were subjected to statistical treatment using analysis of covariance (ANCOVA). In all the cases 0.05 level of confidence was fixed to test the significance. When the obtain ‘F’ ratio was significant. Scheffe’s post hog test was used to find out the paired mean difference. Within the limitations set for this study, it was concluded, that both the experimental group were significantly improved cardiorespiratory endurance than the control. However High Intensity Aerobic training shows better effect (F=6.41*) than the Low Intensity training. Hence, it was recommended that include of small sided games during High Intensity Aerobic training may supports to the players to improve physiological status, ability to tolerate different positional demand and reduce monotonous.
Keywords: High intensity aerobic; Low intensity aerobic; cardiorespiratory endurance